P53 Deficiency Accelerate Esophageal Epithelium Intestinal Metaplasia Malignancy - Quanpeng Qiu; Gang Guo; Xiaolong Guo; Xiake Hu; Tianyu Yu; Gaixia Liu; Haowei Zhang; Yinnan Chen; Junjun She (Biomedicines, 2023)
Barrett’s esophagus (BE) is a precancerous lesion of esophageal adenocarcinoma (EAC). It is a pathological change in which the squamous epithelium distal esophagus is replaced by columnar epithelium. Loss of P53 is involved in the development of BE and is taken as a risk factor for the progression. We established a HET1A cell line with P53 stably knockdown by adenovirus vector infection, followed by 30 days of successive acidic bile salt treatment. MTT, transwell assay, and wound closure assay were applied to assess cell proliferation and migration ability. The expression of key factors was analyzed by RT-qPCR, western blotting and immunohistochemical staining. Our data show that the protein expression level of P53 reduced after exposure to acidic bile salt treatment, and the P53 deficiency favors the survival of esophageal epithelial cells to accommodate the stimulation of acidic bile salts. Furthermore, exposure to acidic bile salt decreases cell adhesions by repressing the JAK/STAT signaling pathway and activating VEGFR/AKT in P53-deficient esophageal cells. In EAC clinical samples, P53 protein expression is positively correlated with that of ICAM1 and STAT3 and negatively correlated with VEGFR protein expression levels. These findings elucidate the role of P53 in the formation of BE, explain the mechanism of P53 deficiency as a higher risk of progression for BE formation, and provide potential therapeutic targets for EAC.